Efektivitas LKPD Berbasis Inkuiri untuk Meningkatkan Kemampuan Komunikasi IPA Peserta Didik - Wahyudi, Zulfa Zachri; Salsabila, Khalis; Khairiyah, Nadiyah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to test the effectiveness of inquiry-based worksheets to improve students' natural science communication skills. The research design used in this study was a quasi-experimental. The population of this study was fourth grade students at a private school for the 2022/2023 school year. Of the two existing classes, one class was selected, namely class IV A as the sample. Data collection techniques in this study were carried out by interviews, tests, and observations. The research instruments used were (1) research instruments including learning implementation plans, (2) data collection instruments including test instruments in the form of pre-test and post-test evaluation question sheets. from the gain index of science communication skills obtained in class IV A, which is 0.79 or 79.49%. Furthermore, the N-Gain Score which is 0.79 is in the high category because the N-Gain Score is 0.79 > 0.7. So the increase in the science communication skills of students who use inquiry-based worksheets is in the high category, meaning that the science communication skills of students who use inquiry-based worksheets experience a significant increase compared to before learning. Keywords: Inquiry, LKPD Effectiveness, and Communication Skills